EFETIVITAS PENGGUNAAN MEDIA KOMIK POP-UP BOOK MATEMATIKA TERHADAP MINAT BELAJAR DAN PRESTASI BELAJAR SISWA KELAS IV PADA MATERI BANGUN DATAR SD NEGERI MEJING 2 - Kurniawan, Zahri; Fadhly Noor Muhammad, Azamul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aimed to assess the effectiveness of Pop-Up Books in teaching geometric forms to fourth-grade pupils at Mejing II Elementary School. This research employed a quasi-experimental design alongside a quantitative methodology. Twenty-eight pupils were selected from each of two classes: the experimental group and the control group. Data were gathered using a learning interest questionnaire and pre- and post-assessments for academic progress. An Independent Samples T-test, a homogeneity test, and a normality test were employed to evaluate the data. The research indicates that the average learning interest of students in the experimental class rose from 44.32 to 48.89 with the introduction of the pop-up math comic books. The Independent Samples T-test for the learning interest variable produced a significance value (Sig. 2-tailed) of 0.024, which is less than 0.05. The experimental class achieved a post-test mean score of 75.68, whereas the control class scored 72.14, resulting in a significant value (Sig. 2-tailed) of 0.038, which is less than 0.05. consequently, the engagement and academic performance of fourth-grade pupils at Mejing II Elementary School in the topic of planar figures improved through the use of Pop-Up Book mathematics media.